A PSYCHIATRIC APPROACH TO SCHOOL ACHIEVEMENT - Sloman, Leon (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1967)
As teachers become aware of the varied causes of poor school achievement, and the serious problem it may pose, they are turning more and more for consultation to professions such as child psychiatry. Psychiatrists who work with seriously disturbed children are also coming to recognize that those who regulate the child’s learning experieIice are important partners in their efforts to help the child. Furthermore, improved medical management has led to an increased survival of multiply-handicapped children and the public school system has been expanding its programs for groups such as the mildly retarded, hard of hearing, poor sighted, emotionally disturbed, reading disordered, and aphasic. As a result, teachers are turning to hospital-based facilities for help with these children.